An exploration of agro-food chain distributive, procedural and interactional fairness in food products - Samoggia, Antonella; Argiriou, Anagnostis; Mallidis, Ioannis; Früh, Simon; Beyhan, Zeynep; Fantini, Andrea; Ettinger, Tamara; Mouchtaropoulou, Evangelia; Benmehaia, Amine M.; Parodos, Leonidas; Gianotti, Andrea; Archour, Lofti; et al. (Frontiers in Sustainable Food Systems, 2023)
Fairness and ethical values in agro-food chain lay at the center of the current debate on agro-food chain sustainability. The food labels may contain elements focused on agro-food chain management fairness practices. The objective of the present study is to explore what types of fairness agro-food companies value in the food products they commercialize, and if the characteristics of agro-food companies have a relationship with the type of fairness valued. The research study collected 226 commercialized food products containing information on the agro-food chain fairness practices companies adopted to produce the food products. Data elaboration included a cluster analysis to identify groups of fair products, and a multinomial logistic regression to explore the relationship between the identified clusters and fairness types, organic, nutritional and functional claims, and price. Results support that fairness-oriented products provide information on different types of fairness that is distributive, procedural, and interactional. Some products provide economic information on the distribution of price between upstream and downstream actors. Other products focus on procedural and interactional fairness practices, such as dignity, respect and transparent relationship in agro-food chain; technologies used in the production and distribution of the product; and ethical certifications that companies hold. Fairness-oriented information differ depending both on the type of chain actor commercializing the product, and on the type of brand, that is whether commercial brand or private label. The main conclusion is that companies convey fairness-related information to consumers differently according to company’s role in the agro-food chain. Yet, there is need to exploit further the potential role of fairness practices in defining effective business strategies to contribute to higher equity and sustainability in the agro-food system.